Pengaruh Pembentukan Sovereign Wealth Fund (SWF) Danantara terhadap Harga Saham dan Return Saham Anggota Danantara - Syahputra, Nanda Riski; Muzakir, Muzakir; Lishanti, Tio Devi (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
The capital market is one indicator reflecting investor response to government economic policies. The establishment of the Danantara Sovereign Wealth Fund (SWF) as a state investment management institution is expected to impact stock prices and stock returns of its member companies. This study aims to analyze the differences in stock prices and stock returns of Danantara member companies before and after the establishment of the Danantara SWF on the Indonesia Stock Exchange. This study uses a quantitative approach with an event study method based on the semi-strong form of the Efficient Market Hypothesis. The data used are secondary data on closing stock prices and daily stock returns for 10 trading days before and 10 trading days after the establishment of Danantara. The study sample consisted of 11 companies selected using a purposive sampling technique. Data analysis was performed using descriptive statistics, the Shapiro-Wilk normality test, and the Wilcoxon Signed Rank Test. The results show no significant difference in the stock prices of Danantara member companies before and after the establishment of the Danantara SWF. Conversely, stock returns show a significant difference, indicating that the market responded more quickly to information about Danantara's formation through changes in stock returns than changes in stock prices.